Resin composition for electrode base for nonaqueous electrolyte secondary battery, electrode base for nonaqueous electrolyte secondary battery, electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
The polyurethane resin composition with a hydroxyl group-containing polyolefin addresses adhesion and swelling issues in non-aqueous electrolyte secondary batteries, enhancing battery performance through improved adhesion and cycle characteristics.
Patent Information
- Application Number
- JP2020106293
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-12
- Filing Date
- 2020-06-19
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-06-19
AI Technical Summary
Existing electrode binders for non-aqueous electrolyte secondary batteries, such as polyvinylidene fluoride, suffer from poor adhesion between active materials and metal current collectors, and have inadequate swelling resistance against electrolytes, leading to decreased battery capacity and poor electrochemical stability.
A resin composition for an electrode binder containing a polyurethane resin composed of a hydroxyl group-containing polyolefin modified with an unsaturated (poly)carboxylic acid anhydride and an amino alcohol, with a specific weight ratio of ethylene to α-olefin monomers, providing enhanced adhesion and swelling resistance.
The resin composition exhibits excellent swelling resistance and adhesion, resulting in improved high voltage charge/discharge cycle characteristics of non-aqueous electrolyte secondary batteries.
Smart Images

Figure 0007605593000001 
Figure 0007605593000002 
Figure 0007605593000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition for an electrode binder for a non-aqueous electrolyte secondary battery, an electrode binder for a non-aqueous electrolyte secondary battery, an electrode for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In non-aqueous electrolyte secondary batteries such as lithium ion batteries, the positive and negative active materials are bonded to the metal collectors of the electrodes by a binder to form the electrodes. The binder is required to have resistance to swelling in the electrolyte, and the positive electrode binder is particularly required to have resistance to oxidation, so a solution of polyvinylidene fluoride dissolved in N-methyl-2-pyrrolidone (NMP) is used as the binder. However, polyvinylidene fluoride has poor adhesion between the active material and the metal collectors of the electrodes, and also has poor resistance to swelling in the electrolyte (hereinafter, sometimes simply referred to as swelling resistance), so there was a problem in terms of electrochemical stability, in that the battery capacity decreases with repeated charging and discharging of the secondary battery (i.e., poor cycle characteristics). In addition, from the viewpoint of reducing environmental load, it is desired to use an aqueous binder that does not contain an organic solvent such as NMP. To solve this problem, a method of using an aqueous dispersion of an olefin polymer that has little swelling in the electrolyte and is electrochemically stable as a binder (for example, see Patent Document 1) is known. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-251856 Summary of the Invention [Problem to be solved by the invention]
[0004] However, in the method described in Patent Document 1, although the composition has swelling resistance to the electrolyte, the adhesion between each active material of the positive and negative electrodes and each electrode metal current collector is still insufficient, and the composition is not satisfactory in terms of electrochemical stability, and improvement is eagerly desired. An object of the present invention is to provide a resin composition for electrode binders for nonaqueous electrolyte secondary batteries, which has excellent swelling resistance to the electrolyte and excellent adhesion between each active material of the positive and negative electrodes and each electrode metal current collector. [Means for solving the problem]
[0005] As a result of investigations aimed at achieving the above object, the present inventors arrived at the present invention. That is, the present invention provides a resin composition for an electrode binder for a non-aqueous electrolyte secondary battery, comprising a polyurethane resin (U), the polyurethane resin (U) being a polyurethane resin obtained by reacting an active hydrogen group-containing compound (W) with an isocyanate component (B), the active hydrogen group-containing compound (W) comprising a polymer polyol (A), the polymer polyol (A) comprising a hydroxyl group-containing polyolefin (A1), the hydroxyl group-containing polyolefin (A1) is a reaction product of an acid-modified polyolefin (X), which is a polyolefin (A01) having a carbon-carbon double bond modified with an unsaturated (poly)carboxylic acid (anhydride) (E), and an aminoalcohol (G), or a reaction product of the acid-modified polyolefin (X) and an alkylene oxide; a resin composition for an electrode binder for a non-aqueous electrolyte secondary battery, in which a weight ratio [ethylene / α-olefin] of ethylene, which is a constituent monomer of the hydroxyl group-containing polyolefin (A1), to an α-olefin is 5 / 95 to 65 / 35, and the isotacticity of the α-olefin portion of the hydroxyl group-containing polyolefin (A1) is 1 to 50%; an electrode binder for a non-aqueous electrolyte secondary battery comprising the resin composition for an electrode binder for a non-aqueous electrolyte secondary battery; an electrode for a non-aqueous electrolyte secondary battery comprising an active material, a metal current collector, and the resin composition for an electrode binder for a non-aqueous electrolyte secondary battery; and a non-aqueous electrolyte secondary battery comprising an electrolyte, a separator, and the electrode for a non-aqueous electrolyte secondary battery. Effect of the Invention
[0006] The resin composition for an electrode binder for a non-aqueous electrolyte secondary battery of the present invention has the following effects. (1) Excellent swelling resistance against electrolyte. (2) Excellent adhesion between the positive and negative active materials and the metal current collectors. (3) A secondary battery having an electrode formed using the resin composition for an electrode binder for a nonaqueous electrolyte secondary battery has excellent high-voltage charge-discharge cycle characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The resin composition for electrode binders for non-aqueous electrolyte secondary batteries of the present invention contains a polyurethane resin (U) and may contain a catalyst, reaction by-products, unreacted materials, and the like used in producing the polyurethane resin (U).
[0008] <Polyurethane resin (U)> The polyurethane resin (U) in the present invention is a polyurethane resin obtained by reacting the active hydrogen group-containing compound (W) with the isocyanate component (B). Note that (U) may have a urea group, and in that case, (U) is a polyurethane urea resin.
[0009] The active hydrogen group-containing compound (W) includes a polymer polyol (A).
[0010] The high molecular weight polyol (A) is a polyol containing a hydroxyl group-containing polyolefin (A1).
[0011] <Hydroxyl-containing polyolefin (A1)> The hydroxyl group-containing polyolefin (A1) in the present invention can be obtained, for example, by reacting an acid-modified polyolefin (X) in which a polyolefin (A01) having a carbon-carbon double bond described below is modified with an unsaturated (poly)carboxylic acid (anhydride) (E) with an amino alcohol (G), or by reacting the acid-modified polyolefin (X) with an alkylene oxide (hereinafter abbreviated as AO).
[0012] The polyolefin (A01) contains ethylene and an α-olefin (having 3 to 8 carbon atoms) as constituent monomers. The α-olefin (having 3 to 8 carbon atoms) is an α-olefin having 3 to 8 carbon atoms, and examples of the α-olefin include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, and 1-octene. Although two or more kinds of α-olefins may be used in combination, it is preferable to use one kind. Of the above α-olefins, from the viewpoints of swelling resistance and charge / discharge cycle characteristics, linear α-olefins (having 3 to 8 carbon atoms) are preferred, linear α-olefins (having 3 to 6 carbon atoms) are more preferred, and propylene is particularly preferred.
[0013] The weight ratio of ethylene and α-olefin (having 3 to 8 carbon atoms), which are constituent monomers of the polyolefin (A01), [ethylene / α-olefin] is 5 / 95 to 65 / 35, preferably 10 / 90 to 60 / 40, and more preferably 15 / 85 to 40 / 60. The weight ratio of ethylene to α-olefin having 3 to 8 carbon atoms in the polyolefin (A01) is directly reflected in the weight ratio of ethylene to α-olefin having 3 to 8 carbon atoms in the hydroxyl group-containing polyolefin (A1), so if the weight ratio [ethylene / α-olefin] is less than 5 / 95 or exceeds 65 / 35, the charge / discharge cycle characteristics are inferior. The weight ratio [ethylene / α-olefin] is, for example, 1 The weight ratio of ethylene to α-olefin having 3 to 8 carbon atoms in the polyolefin (A01) can be adjusted by the weight ratio of ethylene to α-olefin having 3 to 8 carbon atoms in the high molecular weight polyolefin (A00) used as the raw material, which will be described later.
[0014] The (A01) may contain other monomers as constituent monomers in addition to ethylene and α-olefins (having 3 to 8 carbon atoms). In this case, the weight of the other monomers is preferably 10% by weight or less, more preferably 5% by weight or less, and particularly preferably 1% by weight or less, based on the weight of all monomers constituting (A01). Examples of the other monomers include 2-butene, isobutene, α-olefins having a carbon number [sometimes abbreviated as C] of 9 to 30 (1-decene, 1-dodecene, etc.), and unsaturated monomers having a carbon number of 4 to 30 (for example, vinyl acetate).
[0015] The number average molecular weight (Mn) of the polyolefin (A01) is preferably from 800 to 5,800, more preferably from 900 to 4,800, and particularly preferably from 1,000 to 3,800, from the viewpoints of swelling resistance and adhesiveness.
[0016] In the present invention, the conditions for measuring Mn and weight average molecular weight (Mw) of the hydroxyl group-containing polyolefin (A1), polyolefin (A01), high molecular weight polyolefin (A00) described below, and polyurethane resin by GPC (gel permeation chromatography) are as follows. Apparatus: High temperature gel permeation chromatograph ["Alliance GPC V2000", Waters, Inc.] Detector: Refractive index detector Solvent: orthodichlorobenzene Reference material: Polystyrene Sample concentration: 3mg / ml Column stationary phase: PLgel 10μm, MIXED-B 2 columns in series [Manufactured by Polymer Laboratories, Inc.] Column temperature: 135℃
[0017] The number of double bonds per 1,000 carbon atoms in the polyolefin (A01) [the number of carbon-carbon double bonds at the molecular terminals and / or in the molecular chain of (A01)] is preferably 1 to 30, more preferably 1.5 to 20, and particularly preferably 2 to 15, from the viewpoints of reactivity with the (poly)carboxylic acid (anhydride) (E) described below and productivity. In this case, the number of double bonds is 1It can be obtained from a spectrum by H-NMR (nuclear magnetic resonance) spectroscopy. That is, the peaks in the spectrum are assigned, and the relative value between the number of double bonds in (A01) and the number of carbon atoms in (A01) is obtained from the integral value derived from the double bonds in (A01) at 4.5 to 6 ppm and the integral value derived from (A01), and the number of double bonds in the molecular terminal and / or molecular chain per 1,000 carbons in (A01) is calculated. The number of double bonds in the examples described later follows this method.
[0018] The isotacticity of the α-olefin portion of the polyolefin (A01) is preferably from 1 to 50%, and more preferably from 5 to 45%, from the viewpoints of adhesion and storage stability. The isotacticity of the α-olefin portion of the polyolefin (A01) tends to be directly reflected in the isotacticity of the α-olefin portion of the acid-modified polyolefin (X) and the hydroxyl-modified polyolefin (A1) described below. Also, the isotacticity of the α-olefin portion of the polyolefin (A01) tends to be reflected in the isotacticity of the α-olefin portion of the raw material polyolefin (A00) described below, so it can be adjusted by the raw material polyolefin (A00) used.
[0019] The isotacticity can be, for example, 13 It can be calculated using C-NMR (nuclear magnetic resonance spectroscopy). In general, it is known that a side chain methyl group is affected by the configuration (meso or racemo) of the methyl groups on both sides (triad), on both sides of the triad (pentad), and on both sides of the pentad (heptad), and peaks are observed at different chemical shifts. The stereoregularity is generally evaluated for the pentad, and the isotacticity in the present invention can also be calculated based on the evaluation of the pentad. That is, when the α-olefin is propylene, 13Regarding the carbon peaks derived from the side chain methyl groups in propylene obtained by C-NMR, when each pentad peak (H) and a peak derived from the methyl groups in isotactic propylene in which the pentad is formed only of mesostructure (Ha) are taken as the peaks, isotacticity is calculated by the following formula. Isotacticity (%) = [(Ha) / Σ(H)] × 100 (1) In the formula, Ha is the peak height of the isotactic signal (the pentad is formed only in the mesostructure), and H is the height of each peak of the pentad. The isotacticity of the α-olefin moiety of (A01) and (X) can also be measured in the same manner as above.
[0020] The polyolefin (A01) can be produced, for example, by thermally degrading a high molecular weight (preferably Mn of 60,000 to 400,000, more preferably Mn of 80,000 to 250,000) polyolefin (A00).
[0021] The thermal degradation method includes a method of thermally degrading the high molecular weight polyolefin (A00) (1) in the absence of an organic peroxide, for example, at 300 to 450°C for 0.5 to 10 hours, and (2) in the presence of an organic peroxide [for example, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane], for example, at 180 to 300°C for 0.5 to 10 hours. Of these, from the industrial viewpoint and from the viewpoint of modification properties, the method (1) is preferred, which is capable of easily obtaining a polymer having a larger number of double bonds at the molecular terminals and / or in the molecular chain.
[0022] The weight ratio [ethylene / α-olefin] of the monomers constituting the above (A01) to ethylene and α-olefin tends to be the same as the weight ratio [ethylene / α-olefin] of the high molecular weight polyolefin (A00). Furthermore, the higher the thermal degradation temperature and the longer the thermal degradation time, the larger the number of double bonds per 1,000 carbon atoms tends to be. Furthermore, the smaller the Mn of (A00), the higher the thermal degradation temperature, and the longer the thermal degradation time, the smaller the Mn of (A) tends to be. In addition, the higher the isotacticity of (A00), the higher the isotacticity of (A01) tends to be.
[0023] The unsaturated (poly)carboxylic acid (anhydride) (E) includes (poly)carboxylic acid (anhydride) having one polymerizable unsaturated group and having 3 to 30 carbon atoms [hereinafter sometimes abbreviated as C]. In the present invention, the unsaturated (poly)carboxylic acid (anhydride) means an unsaturated monocarboxylic acid, an unsaturated polycarboxylic acid and / or an unsaturated polycarboxylic acid anhydride.
[0024] Among the (E), examples of the unsaturated monocarboxylic acid include aliphatic monocarboxylic acids (C3-24, such as acrylic acid, methacrylic acid, α-ethylacrylic acid, crotonic acid, and isocrotonic acid), and alicyclic monocarboxylic acids (C6-24, such as cyclohexene carboxylic acid); examples of the unsaturated poly(2-3 or more) carboxylic acids (anhydrides) include unsaturated dicarboxylic acids (anhydrides) [aliphatic dicarboxylic acids (anhydrides) (C4-24, such as maleic acid, fumaric acid, itaconic acid, citraconic acid, and mesaconic acid, and anhydrides thereof), and alicyclic dicarboxylic acids (anhydrides) (C8-24, such as cyclohexene dicarboxylic acid, cycloheptene dicarboxylic acid, bicycloheptene dicarboxylic acid, methyltetrahydrophthalic acid, and anhydrides thereof)]. (E) may be used alone or in combination of two or more. Among the above (E), from the viewpoints of reactivity with the polyolefin (A01) and mechanical strength, unsaturated dicarboxylic acid anhydrides are preferred, and maleic anhydride is more preferred.
[0025] <Acid-modified polyolefin (X)> The acid-modified polyolefin (X) in the present invention contains the polyolefin (A01) having a carbon-carbon double bond and the unsaturated (poly)carboxylic acid (anhydride) (E) as constituent units, and is preferably obtained by reacting the polyolefin (A01) with the unsaturated (poly)carboxylic acid (anhydride) (E) in the absence or presence of a radical initiator.
[0026] From the viewpoint of swelling resistance and adhesiveness, the weight ratio of (A01) to (E) [(A01) / (E)] is preferably 80 / 20 to 99.5 / 0.5, and more preferably 90 / 10 to 99 / 1.
[0027] The acid-modified polyolefin (X) can be produced by reacting the polyolefin (A01) and the unsaturated (poly)carboxylic acid (anhydride) (E) with an appropriate organic solvent [C3 to C18, for example, hydrocarbons (hexane, heptane, octane, dodecane, benzene, toluene, xylene, etc.), halogenated hydrocarbons (di-, tri-, and tetrachloroethane, dichlorobutane, etc.), ketones (acetone, methyl ethyl ketone, di-t-butyl ketone, etc.), ethers (ethyl-n-propyl ether, di-n-butyl ether, di-t-butyl ether, dioxane, etc.)], if necessary, in the presence of a radical initiator (F). The radical initiator (F) may be a known one, for example, an azo initiator (azobisisobutyronitrile, etc.) or a peroxide initiator (dicumyl peroxide, etc.). Among the above (F), peroxide initiators are preferred.
[0028] The reaction temperature is preferably 100 to 270°C, more preferably 120 to 250°C, and particularly preferably 130 to 240°C, from the viewpoints of the reactivity of (A01) and (E) and productivity.
[0029] From the viewpoint of charge-discharge cycle characteristics, the acid value of the acid-modified polyolefin (X) is preferably 1 to 130 mgKOH / g, more preferably 3 to 75 mgKOH / g, and particularly preferably 5 to 50 mgKOH / g. The acid value here is a value measured according to the following procedures (i) to (iii) in accordance with JIS K0070:1992. (i) Dissolve 1 g of (X) in 100 g of xylene adjusted to 100°C. (ii) At the same temperature, titration is performed with 0.1 mol / L potassium hydroxide ethanol solution [product name "0.1 mol / L ethanolic potassium hydroxide solution", manufactured by Wako Pure Chemical Industries, Ltd.] using phenolphthalein as an indicator. (iii) Convert the amount of potassium hydroxide required for the titration into mg to calculate the acid value (unit: mgKOH / g). In addition, the above measurement gives the result that one acid anhydride group is equivalent to one carboxyl group. The acid value can be appropriately adjusted by the number of double bonds in (A01), the weight of (A01), the type of (E), and the weight of (E).
[0030] From the viewpoints of solvent solubility and swelling resistance, the Mn of the acid-modified polyolefin (X) is preferably from 900 to 5,900, more preferably from 900 to 5,000, and particularly preferably from 900 to 4,000.
[0031] The isotacticity of the α-olefin portion of the acid-modified polyolefin (X) is preferably from 1 to 50%, more preferably from 5 to 45%, and particularly preferably from 10 to 40%, from the viewpoints of solvent solubility and adhesiveness.
[0032] Examples of the hydroxyl-modified polyolefin (A1) in the present invention include a reaction product of an acid-modified polyolefin (X) with an aminoalcohol (G) and a reaction product of an acid-modified polyolefin (X) with AO.
[0033] Examples of the amino alcohol (G) include linear alkanolamines, cycloalkanolamines and alkylalkanolamines having 2 to 12 carbon atoms (e.g., 2-aminoethanol, 3-aminopropanol, 1-amino-2-propanol, 2-amino-2-methyl-1-propanol, 4-aminobutanol, 5-aminopentanol, 6-aminohexanol, diethanolamine, di-n- or isopropanolamine, 3-aminomethyl-3,5,5-trimethylcyclohexanol, methylethanolamine and ethylethanolamine), and from the viewpoint of charge-discharge cycle characteristics, 2-aminoethanol is preferred.
[0034] Examples of AO include AOs having 2 to 12 carbon atoms (ethylene oxide, 1,2- or 1,3-propylene oxide, 1,2-, 2,3- or 1,3-butylene oxide, tetrahydrofuran, 3-methyltetrahydrofuran, styrene oxide, and α-olefin oxide, etc.), and from the viewpoint of adhesion to the substrate, AOs having 2 to 4 carbon atoms are preferred, and ethylene oxide and propylene oxide are more preferred. One type of AO may be used alone, or two or more types may be used in combination. The number of moles of AO added per carboxy group of (X) is preferably 1 to 10 moles or more, more preferably 1 to 5 moles, and particularly preferably 1 mole, from the viewpoint of charge-discharge cycle characteristics.
[0035] The modification of (X) with amino alcohol (G) can be carried out by a known method, for example, by adding an excess (for example, 1.1 to 2 times the molar amount or more) of amino alcohol to the carboxyl group (carbonyl group in the case of anhydride) of (X) to react, and then removing the unreacted amino alcohol by a method such as distillation. The reaction can be carried out in the presence or absence of an organic solvent. The reaction temperature is preferably 100 to 220°C, more preferably 120 to 200°C, from the viewpoints of reaction rate and reaction stability. The modification of (X) with AO is carried out by a known method. For example, the reaction temperature when carrying out ring-opening addition polymerization of AO is preferably 40 to 200°C, more preferably 70 to 160°C, from the viewpoints of reaction rate and reaction stability. The reaction pressure is preferably -0.1 to 0.5 MPa. The reaction is carried out in the presence of a catalyst as necessary.
[0036] The weight ratio of ethylene and α-olefin (having 3 to 8 carbon atoms) which are constituent monomers of the hydroxyl-modified polyolefin (A1) [ethylene / α-olefin] is 5 / 95 to 65 / 35, preferably 10 / 90 to 60 / 40, and more preferably 15 / 85 to 40 / 60. If the weight ratio [ethylene / α-olefin] is less than 5 / 95 or exceeds 65 / 35, the charge / discharge cycle characteristics are inferior. The weight ratio of ethylene and the α-olefin having 3 to 8 carbon atoms, which are the constituent monomers of the hydroxyl-modified polyolefin (A1), can be appropriately adjusted by the ratio of ethylene and the α-olefin having 3 to 8 carbon atoms used in (A00).
[0037] The isotacticity of the α-olefin portion of the hydroxyl group-containing polyolefin (A1) is 1 to 50%, preferably 5 to 45%. If the isotacticity of the α-olefin portion of (A1) is less than 1%, the adhesiveness is poor, and if it exceeds 50%, the solvent solubility is poor. The isotacticity of the α-olefin portion of the hydroxyl group-containing polyolefin (A1) can be appropriately adjusted by the isotacticity of (A01).
[0038] The Mn of the hydroxyl group-containing polyolefin (A1) is preferably 500 or more, and from the viewpoint of charge-discharge cycle characteristics, it is preferably 1,000 to 10,000, more preferably 1,100 to 7,500, and particularly preferably 1,400 to 5,500. Mn of (A1) can be appropriately adjusted by controlling Mn of (A01), the type and amount of (E) used, and the reaction between (A01) and (E).
[0039] The hydroxyl value (mgKOH / g) of the hydroxyl-containing polyolefin (A1) is preferably from 12 to 120, more preferably from 15 to 110, and particularly preferably from 20 to 80, from the viewpoint of adhesiveness. The hydroxyl value of (A1) can be appropriately adjusted by the number of double bonds in (A01), the amount of (A01) used, the type and amount of (E) used, and the type and amount of (G) or AO used. The acid value (mgKOH / g) of (A1) is preferably 0 to 50, and more preferably 0 to 30, from the viewpoint of swelling resistance. The hydroxyl value and acid value of (A1) are values measured in accordance with JIS K0070-1992.
[0040] In the present invention, the number of hydroxyl groups per molecule of the hydroxyl-modified polyolefin (A1) is preferably 1.5 to 2.0, more preferably 1.6 to 2.0, from the viewpoint of adhesiveness. The number of hydroxyl groups per molecule of the hydroxyl-modified polyolefin (A1) can be calculated by the following mathematical formula (1). Number of hydroxyl groups per molecule = Mn A1 ×OHV / 56100 (1) Mn A1 : (A1) Mn OHV: Hydroxyl value of (A1) (mgKOH / g)
[0041] When the polyurethane resin (U) uses multiple types of hydroxyl-modified polyolefins (A1), the weight average number of hydroxyl groups in all of the hydroxyl-modified polyolefins (A1) constituting the polyurethane resin (U) is preferably 1.5 to 2.0, and more preferably 1.6 to 2.0, from the viewpoint of the adhesion of the polyurethane resin (U) to the substrate.
[0042] As the polymer polyol (A) other than the hydroxyl group-containing polyolefin (A1), one or more of condensation type polyester polyol (A2), polylactone polyol (A3), polycarbonate polyol (A4), polyether polyol (A5) and polyacrylic polyol (A6) can be used in combination. (A) may be used alone or in combination of two or more. The above (A2) to (A6) are also referred to as polymer polyol (A2) to polymer polyol (A6). The Mn of the high molecular weight polyol (A) other than the hydroxyl group-containing polyolefin (A1) is preferably 500 or more, more preferably 500 to 5,000, and particularly preferably 1,000 to 4,000, from the viewpoint of adhesiveness.
[0043] Examples of the condensation type polyester polyol (A2) include those obtained by condensing a diol having an Mn of less than 500 with a dicarboxylic acid other than terephthalic acid or an ester-forming derivative thereof [such as an acid anhydride, a lower (C1 to C4) alkyl ester, and an acid halide].
[0044] Examples of diols having an Mn of less than 500 include aliphatic dihydric alcohols having 2 to 8 carbon atoms [linear diols (ethylene glycol, diethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, etc.) and diols having branched alkyl chains (1,2-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2,2-diethyl-1,3-propanediol, 1,2-, 1,3- or 2,3-butanediol, etc.)]; alicyclic group-containing dihydric alcohols [1,4-bis(hydroxymethyl)cyclohexane, 2,2-bis(4-hydroxycyclohexyl)propane, etc.]; aromatic ring-containing dihydric alcohols having 8 to 20 carbon atoms [m- or p-xylylene glycol, bis(hydroxyethyl)benzene, bis(hydroxyethoxy)benzene]; AO adducts of bisphenols (bisphenol A, bisphenol S, bisphenol F, etc.), AO adducts of dihydroxynaphthalene, bis(2-hydroxyethyl)terephthalate, etc.]. Diols having an Mn of less than 500 may be used alone or in combination of two or more.
[0045] Examples of dicarboxylic acids or their ester-forming derivatives include aliphatic dicarboxylic acids having 2 to 15 carbon atoms [oxalic acid, succinic acid, adipic acid, sebacic acid, glutaric acid, azelaic acid, maleic acid, fumaric acid, etc.], aromatic dicarboxylic acids having 8 to 12 carbon atoms [terephthalic acid, phthalic acid, isophthalic acid, etc.], and their ester-forming derivatives [acid anhydrides, lower alkyl esters (dimethyl esters, diethyl esters, etc.), acid halides (acid chlorides, etc.)], etc. One type of dicarboxylic acid may be used alone, or two or more types may be used in combination.
[0046] Specific examples of the condensation type polyester polyol (A2) include polyethylene adipate diol, polybutylene adipate diol, polyhexamethylene adipate diol, polyhexamethylene isophthalate diol, polyneopentyl adipate diol, polyethylene propylene adipate diol, polyethylene butylene adipate diol, polybutylene hexamethylene adipate diol, poly(polyoxytetramethylene) adipate diol, poly(3-methylpentylene adipate) diol, polyethylene azelate diol, polyethylene sebacate diol, polybutylene azelate diol, and polybutylene sebacate diol, etc. (A2) may be used alone or in combination of two or more.
[0047] The polylactone polyol (A3) may be one obtained by ring-opening polymerization of lactone monomers (γ-butyrolactone, γ-valerolactone, ε-caprolactone, and mixtures of two or more of these, etc.) using the above-mentioned diol having an Mn of less than 500 as an initiator. Specific examples of the polylactone polyol (A3) include polybutyrolactone diol, polyvalerolactone diol, and polycaprolactone diol. (A3) may be used alone or in combination of two or more.
[0048] The polycarbonate polyol (A4) may be a polycarbonate diol produced by condensing the diol having an Mn of less than 500 with a low molecular weight carbonate compound (for example, a dialkyl carbonate having an alkyl group with 1 to 6 carbon atoms, an alkylene carbonate having an alkylene group with 2 to 6 carbon atoms, and a diaryl carbonate having an aryl group with 6 to 9 carbon atoms) while causing a dealcoholization reaction. One type of (A4) may be used alone, or two or more types may be used in combination.
[0049] Specific examples of the polycarbonate polyol (A4) include polyhexamethylene carbonate diol, polypentamethylene carbonate diol, polytetramethylene carbonate diol, and poly(tetramethylene / hexamethylene) carbonate diol (for example, a diol obtained by condensing 1,4-butanediol and 1,6-hexanediol with a dialkyl carbonate while causing a dealcoholization reaction).
[0050] Examples of the polyether polyol (A5) include the above-mentioned AO adducts having 2 to 12 carbon atoms to the diols having an Mn of less than 500. The AO may be used alone or in combination of two or more types as block copolymers or random copolymers.
[0051] Among the polyether polyols (A5), those having a branched alkyl chain are preferred from the viewpoint of resolubility, i.e., those using as a raw material a diol having a branched alkyl chain among diols having an Mn of less than 500, those using 1,2-propylene oxide, 1,2-, 2,3- or 1,3-butylene oxide, 3-methyltetrahydrofuran, etc. as AO in the AO adduct, and more preferred are aliphatic polyether diols of dihydric alcohols having a branched alkyl, and particularly preferred is polyoxypropylene glycol. (A5) may be used alone or in combination of two or more kinds.
[0052] The poly(meth)acrylic polyol (A6) is not particularly limited, and examples thereof include homopolymers and copolymers of (meth)acrylic acid esters having a hydroxy group. The (meth)acrylic polyol can also be obtained by copolymerizing a compound having a polymerizable unsaturated bond in addition to a (meth)acrylic acid ester having a hydroxy group. In the present invention, "(meth)acrylic" means "methacrylic and / or acrylic".
[0053] The (meth)acrylic acid ester having a hydroxy group includes those having one (meth)acryloyl group, and examples thereof include those having a hydroxyalkyl group having 2 to 20 carbon atoms {for example, hydroxyalkyl (meth)acrylic acid esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate} and (meth)acrylic acid monoesters of trihydric alcohols {for example, a (meth)acrylic acid monoester of glycerin, a (meth)acrylic acid monoester of trimethylolpropane, and the like}.
[0054] The compound having a polymerizable unsaturated bond includes a compound having one polymerizable unsaturated bond, and examples thereof include (meth)acrylic acid alkyl esters having 4 to 50 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, lauryl (meth)acrylate, glycidyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; unsaturated carboxylic acids having 3 to 50 carbon atoms, such as (meth)acrylic acid, maleic acid, and itaconic acid; unsaturated amides having 3 to 50 carbon atoms, such as (meth)acrylamide, N-methylol (meth)acrylamide, and diacetone (meth)acrylamide; and other polymerizable monomers, such as styrene, vinyl toluene, vinyl acetate, acrylonitrile, and dibutyl fumarate.
[0055] Examples of the polymerization method of the (meth)acrylic acid ester having a hydroxy group or the compound having a polymerizable unsaturated bond include emulsion polymerization, suspension polymerization, dispersion polymerization, solution polymerization, etc. The emulsion polymerization can also be carried out in stages.
[0056] Specific examples of commercially available polyacrylic polyols include "ARUFON UH-2000, UH-2041, UH-2190, UHE-2012" manufactured by Toagosei Co., Ltd., and "Actflow UT-1001, UMM-1001" manufactured by Soken Chemical & Engineering Co., Ltd.
[0057] Among the poly(meth)acrylic polyols (A6), from the viewpoint of compatibility with the hydroxyl group-containing polyolefin (A1), it is preferable to use at least one compound having a polymerizable unsaturated bond selected from the group consisting of n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, lauryl (meth)acrylate and 2-ethylhexyl (meth)acrylate, and more preferably a polyacrylic diol using n-butyl (meth)acrylate and / or 2-ethylhexyl (meth)acrylate. (A6) may be used alone or in combination of two or more kinds.
[0058] When the hydroxyl-containing polyolefin (A1) is used in combination with the condensation type polyester polyol (A2), the polylactone polyol (A3), the polycarbonate polyol (A4), the polyether polyol (A5) and / or the poly(meth)acrylic polyol (A6), the ratio of the weight of the hydroxyl-containing polyolefin (A1) to the total weight of the condensation type polyester polyol (A2), the polylactone polyol (A3), the polycarbonate polyol (A4), the polyether polyol (A5) and the poly(meth)acrylic polyol (A6) is preferably 100:0 to 30:70, more preferably 100:0 to 50:50, from the viewpoints of adhesion and charge / discharge cycle characteristics.
[0059] The number average molecular weight (Mn) and weight average molecular weight (Mw) of the polymer polyol (A) other than the hydroxyl group-containing polyolefin (A1) in the present invention can be measured by gel permeation chromatography, for example, under the following conditions. Apparatus: "Waters Alliance 2695" [Waters] Column: "Guardcolumn Super HL" (1 piece), "TSKgel A combination of one each of SuperH2000, TSKgel SuperH3000, and TSKgel SuperH4000 (all manufactured by Tosoh Corporation) Sample solution: 0.25% by weight tetrahydrofuran solution Solution injection volume: 10μl Flow rate: 0.6ml / min Measurement temperature: 40℃ Detector: Refractive index detector Reference material: Standard polyethylene glycol
[0060] <Isocyanate component (B)> The isocyanate component (B) in the present invention may be an aromatic polyisocyanate (B1) having 6 to 20 carbon atoms (excluding carbon atoms in the isocyanate groups, the same applies below) having 2 to 3 or more isocyanate groups, an aliphatic polyisocyanate (B2) having 2 to 18 carbon atoms, an alicyclic polyisocyanate (B3) having 4 to 15 carbon atoms, an araliphatic polyisocyanate (B4) having 8 to 15 carbon atoms, and a modified product (B5) of (B1) to (B4), etc. The isocyanate component (B) may be used alone or in combination of two or more kinds.
[0061] Examples of the aromatic polyisocyanate (B1) having 6 to 20 carbon atoms include 1,3- or 1,4-phenylene diisocyanate, 2,4- or 2,6-tolylene diisocyanate (TDI), 4,4'- or 2,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthylene diisocyanate, and 4,4',4''-triphenylmethane triisocyanate. Examples of isocyanatophenylsulfonyl isocyanate include m- or p-isocyanatophenylsulfonyl isocyanate and crude MDI.
[0062] Examples of the aliphatic polyisocyanate (B2) having 2 to 18 carbon atoms include ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), dodecamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, and 2-isocyanatoethyl-2,6-diisocyanatohexanoate.
[0063] Examples of the alicyclic polyisocyanate (B3) having 4 to 15 carbon atoms include isophorone diisocyanate (IPDI), 4,4-dicyclohexylmethane diisocyanate (hydrogenated MDI), cyclohexylene diisocyanate, methylcyclohexylene diisocyanate (hydrogenated TDI), bis(2-isocyanatoethyl)-4-cyclohexene-1,2-dicarboxylate, and 2,5- or 2,6-norbornane diisocyanate.
[0064] Examples of the araliphatic polyisocyanate (B4) having 8 to 15 carbon atoms include m- or p-xylylene diisocyanate (XDI) and α,α,α’,α’-tetramethylxylylene diisocyanate (TMXDI).
[0065] Examples of the modified product (B5) of (B1) to (B4) include modified products of (B1) to (B4) having a urethane group, a carbodiimide group, an allophanate group, a urea group, a biuret group, a uretdione group, a uretoimine group, an isocyanurate group, or an oxazolidone group.
[0066] Among the isocyanate components (B), from the viewpoints of mechanical strength and charge / discharge cycle characteristics, the preferred ones are aliphatic polyisocyanates (B2) having 2 to 18 carbon atoms and alicyclic polyisocyanates (B3) having 4 to 15 carbon atoms. More preferred is (B3), and particularly preferred are IPDI and hydrogenated MDI.
[0067] <Chain extender (C) with The polyurethane resin (U) may be prepared by reacting not only the high molecular weight polyol (A) with the isocyanate component (B) but also with a chain extender (C). Examples of the chain extender (C) include a compound (c1) containing an ionic group and two active hydrogen atoms, a polyhydric alcohol (c2) having an Mn or a chemical formula weight of less than 500, water, a polyalkylene polyamine (c3), hydrazine or a derivative thereof (c4), an amino alcohol having 2 to 10 carbon atoms (c5), and a polyepoxy compound having 2 to 30 carbon atoms (c6).
[0068] The compound (c1) containing an ionic group and two active hydrogen atoms is also used for introducing the ionic group into the polyurethane resin (U).
[0069] As the chain extender (C), any one of (c1) to (c6) may be used alone, or any combination of them may be used.
[0070] <Compound (c1) containing an ionic polar group and two active hydrogen atoms> The compound (c1) containing an ionic polar group and two active hydrogen atoms includes a compound (c11) containing an anionic group and an active hydrogen atom and a compound (c12) containing a cationic group and an active hydrogen atom. One type of (c1) may be used alone, or two or more types may be used in combination.
[0071] The anionic group in (c11) means an acid group or a neutralized acid anion group. Examples of (c11) include compounds containing a carboxyl group as an anionic group and having 2 to 10 carbon atoms [dialkylolalkanoic acids (e.g., 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, 2,2-dimethylolheptanoic acid, and 2,2-dimethyloloctanoic acid), tartaric acid, and amino acids (e.g., glycine, alanine, and valine)], compounds containing a sulfonic acid group as an anionic group and having 2 to 16 carbon atoms [3-(2,3-dihydroxypropoxy)-1-propanesulfonic acid, sulfoisophthalic acid di(ethylene glycol) ester, and the like], compounds containing a sulfamic acid group as an anionic group and having 2 to 10 carbon atoms [N,N-bis(2-hydroxylethyl)sulfamic acid, and the like], and salts of these compounds neutralized with a neutralizing agent.
[0072] Examples of the neutralizing agent used for the salt of (c11) include ammonia, an amine compound having 1 to 20 carbon atoms, and an alkali metal hydroxide (sodium hydroxide, potassium hydroxide, lithium hydroxide, etc.). Examples of the amine compound having 1 to 20 carbon atoms include primary amines such as monomethylamine, monoethylamine, monobutylamine, and monoethanolamine; secondary amines such as dimethylamine, diethylamine, dibutylamine, diethanolamine, diisopropanolamine, and methylpropanolamine; and tertiary amines such as trimethylamine, triethylamine, dimethylethylamine, dimethylmonoethanolamine, and triethanolamine.
[0073] As the neutralizing agent used for the salt of (c11), from the viewpoints of the drying property and charge / discharge cycle characteristics of the resulting aqueous polyurethane resin dispersion, a compound having a high vapor pressure at 25° C. is preferable. From such viewpoints, as the neutralizing agent used for the salt of (c11), ammonia, monomethylamine, monoethylamine, dimethylamine, diethylamine, trimethylamine, triethylamine and dimethylethylamine are preferable. The amount of neutralizer used in the salt of (c11) is preferably such that the neutralization rate is 50 to 200%, more preferably 60 to 150%, relative to the amount of acidic groups in the polyurethane resin (U), from the viewpoints of water resistance and dispersion stability of the resin.
[0074] Among (c11), from the viewpoint of charge / discharge cycle characteristics and dispersion stability of the polyurethane resin aqueous dispersion, preferred are 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, and salts thereof, and more preferred are neutralized salts of 2,2-dimethylolpropionic acid and 2,2-dimethylolbutanoic acid with ammonia or an amine compound having 1 to 20 carbon atoms.
[0075] The cationic group in the compound (c12) containing a cationic group and an active hydrogen atom means a group in which a proton is added to a tertiary amino group, an unneutralized tertiary amino group, or a quaternary ammonium group.
[0076] Examples of (c12) include salts obtained by neutralizing compounds such as compounds having a tertiary amino group as the cationic group and a hydroxyl group as the active hydrogen atom, and tertiary amino group-containing diols having 3 to 20 carbon atoms [N-alkyldialkanolamines (e.g., N-methyldiethanolamine, N-propyldiethanolamine, N-butyldiethanolamine, and N-methyldipropanolamine), and N,N-dialkylmonoalkanolamines (e.g., N,N-dimethylethanolamine)] with a neutralizing agent.
[0077] Examples of the neutralizing agent used in (c12) include monocarboxylic acids having 1 to 10 carbon atoms (such as formic acid, acetic acid, propanoic acid, etc.), carbonic acid, dimethyl carbonate, dimethyl sulfate, methyl chloride, and benzyl chloride.
[0078] The neutralizing agent used in (c11) and (c12) may be added at any time before, during, or after the urethanization reaction, or before, during, or after the water dispersion step, but from the viewpoint of the stability of the urethane resin and the stability of the aqueous dispersion, it is preferable to add the neutralizing agent before or during the water dispersion step. In addition, the neutralizing agent that has volatilized during the desolvation may be added after the desolvation, and the type of neutralizing agent to be added may be freely selected from the above.
[0079] Examples of the polyhydric alcohol (c2) having an Mn or a chemical formula weight of less than 500 include dihydric alcohols having 2 to 20 carbon atoms [aliphatic diols (ethylene glycol, propylene glycol, 1,3- or 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, 1,2- or 1,10-decanediol, 1,2- or 1,12-dodecanediol, etc.), alicyclic diols (1,2-, 1,3- or 1,4-cyclohexanediol, cyclohexanedimethanol, etc.), aromatic aliphatic diols {1-phenylethane-1,2-diol, 1,4-bis(hydroxyethyl)benzene, etc.}, ether group-containing diols {3-butoxy-1,2-propanediol, 3 -(2-ethylhexoxy)-1,2-propanediol, 3-phenoxy-1,2-propanediol, 3-(p-tert-butylphenoxy)-1,2-propanediol, etc.} and halogen group-containing diols (3-chloro-1,2-propanediol, etc.)], trihydric alcohols having 3 to 20 carbon atoms (aliphatic triols (glycerin, trimethylolpropane, etc.)), tetrahydric to octahydric alcohols having 5 to 20 carbon atoms (aliphatic polyols (pentaerythritol, sorbitol, mannitol, sorbitan, diglycerin, dipentaerythritol, etc.), and sugars (sucrose, glucose, mannose, fructose, methyl glucoside, and derivatives thereof)].
[0080] Examples of the polyalkylene polyamine (c3) include aliphatic polyamines having 2 to 20 carbon atoms (ethylenediamine, propylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, etc.), alicyclic polyamines having 6 to 20 carbon atoms (diaminocyclohexane, dicyclohexylmethanediamine, isophoronediamine, etc.), aromatic polyamines having 2 to 20 carbon atoms (phenylenediamine, tolylenediamine, diphenylmethanediamine, etc.), and heterocyclic polyamines having 2 to 20 carbon atoms (piperazine, N-aminoethylpiperazine, etc.).
[0081] Examples of the hydrazine or derivatives thereof (c4) include hydrazines (hydrazine and monoalkylhydrazines, etc.), dihydrazides (succinic acid dihydrazide, adipic acid dihydrazide, etc.), and the like.
[0082] Examples of the amino alcohol (c5) having 2 to 10 carbon atoms include ethanolamine, diethanolamine, 2-amino-2-methylpropanol, and triethanolamine.
[0083] Examples of the polyepoxy compound (c6) having 2 to 30 carbon atoms include AO having 2 to 4 carbon atoms, glycidol, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, p-tert-butylphenyl glycidyl ether, 1,2-epoxydecane, 1,2-epoxydodecane, cyclohexene oxide, styrene oxide, epichlorohydrin, 1,6-hexanediol diglycidyl ether, and trimethylolpropane polyglycidyl ether.
[0084] The polyepoxy compound (c6) having 2 to 30 carbon atoms is used as a chain extender when the compound (c1) containing an ionic polar group and two active hydrogen atoms has a carboxyl group, and the epoxy group reacts with the carboxyl group to cause an extension reaction.
[0085] Of the chain extenders (C), from the viewpoints of adhesion and charge / discharge cycle characteristics, preferred are a compound (c1) containing an ionic group and two active hydrogen atoms, a polyhydric alcohol (c2), water, a polyalkylene polyamine (c3), and an amino alcohol (c5), and more preferred are a compound (c1) containing an ionic group and two active hydrogen atoms, a dihydric alcohol, a trihydric alcohol, water, an aliphatic polyamine, an alicyclic polyamine, and an amino alcohol (c5).
[0086] The amount of (c1) used is adjusted so that the content of ionic polar groups in (U) is preferably 0.5 to 5.0% by weight, more preferably 0.5 to 4.8% by weight, and particularly preferably 0.5 to 4.5% by weight, based on the weight of (U). The content of ionic polar groups in the present invention means the weight % of unneutralized cationic groups or anionic groups, and does not include the weight of counter ions. For example, the content of ionic polar groups in (c11) means the weight % of carboxy groups (-COOH) in the case of triethylamine salt of 2,2-dimethylolpropionic acid, and the weight % of sulfo groups (-SO3H) in the case of triethylamine salt of 3-(2,3-dihydroxypropoxy)-1-propanesulfonic acid. The content of ionic polar groups in (c12) means the weight % of only nitrogen atoms in tertiary amino groups.
[0087] In the polyurethane resin (U) of the present invention, a reaction terminator can be used as necessary. Examples of the reaction terminator include monoalcohols having 1 to 8 carbon atoms (methanol, ethanol, isopropanol, cellosolve, carbitol, etc.) and monoamines having 1 to 10 carbon atoms (mono- or di-alkylamines such as monomethylamine, monoethylamine, monobutylamine, dibutylamine, monooctylamine, etc.; mono- or di-alkanolamines such as monoethanolamine, diethanolamine, diisopropanolamine, etc.). The reaction terminators may be used alone or in combination of two or more.
[0088] The polyurethane resin (U) in the present invention may contain additives such as antioxidants, color inhibitors, weather stabilizers, plasticizers, and mold release agents, if necessary. The amount of these additives used is preferably as small as possible based on the weight of (U) from the viewpoint of charge-discharge cycle characteristics, within a range in which the additives can exert their effects, and is preferably 10% by weight or less, more preferably 3% by weight or less, and particularly preferably 1% by weight or less.
[0089] The urethane group content in the polyurethane resin (U) in the present invention is preferably from 0.5 to 3.0 mmol / g, more preferably from 0.7 to 2.5 mmol / g, and particularly preferably from 0.9 to 2.0 mmol / g, from the viewpoint of adhesiveness.
[0090] The urethane group content of the polyurethane resin (U) can be adjusted to a desired range by appropriately adjusting the hydroxyl group-containing polyolefin (A1), the polymer polyol (A) containing the above-mentioned (A2) to (A6) used as necessary, the isocyanate component (B), and, as necessary, the chain extender (C). The urethane group content is determined by the N atom content quantified by a nitrogen analyzer. 1 H-NMR It is calculated from the quantitatively determined ratio of urethane groups to urea groups and the contents of allophanate groups and biuret groups.
[0091] From the viewpoints of swelling resistance and adhesion, the urea group content in the polyurethane resin (U) is preferably 1.5 mmol / g or less, more preferably 1.2 mmol / g or less, particularly preferably 1.0 mmol / g or less, and most preferably 0.8 mmol / g or less, based on the weight of (U).
[0092] The urea group content in the polyurethane resin (U) can be adjusted to fall within a desired range by appropriately adjusting the amino group content, water content and isocyanate group content in the raw materials for (U). The urea group content is determined by the N atom content determined by a nitrogen analyzer. 1It is calculated from the ratio of urethane groups and urea groups and the contents of allophanate groups and biuret groups quantified by H-NMR.
[0093] <Electrode binder for non-aqueous electrolyte secondary batteries> The electrode binder for non-aqueous electrolyte secondary batteries of the present invention contains the polyurethane resin (U), which is the resin composition for electrode binders for non-aqueous electrolyte secondary batteries of the present invention, and may contain a binder resin other than the polyurethane resin (U).
[0094] Examples of binder resins other than the polyurethane resin (U) include starch, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, and polypropylene.
[0095] The electrode binder for non-aqueous electrolyte secondary batteries of the present invention may contain the polyurethane resin (U), which is the resin composition for electrode binders for non-aqueous electrolyte secondary batteries of the present invention. The polyurethane resin (U) is preferably contained in the binder as an aqueous resin dispersion (Q) in which the polyurethane resin (U) is dispersed in a medium containing water.
[0096] <Aqueous resin dispersion (Q)> In the present invention, the aqueous resin dispersion (Q) contains a resin composition for an electrode binder for a non-aqueous electrolyte secondary battery and water.
[0097] The aqueous resin dispersion (Q) can be produced, for example, by the following method.
[0098] (1) A solution (for example, a solvent solution described later) of a polyurethane prepolymer (P) having an isocyanate group at its end and containing a high molecular weight polyol (A) containing a hydroxyl group-containing polyolefin (A1) and an isocyanate component (B) as constituent monomers is prepared. Next, water, and if necessary, a solvent, a chain extender (C) and a neutralizing agent are charged, followed by phase inversion emulsification, and if necessary, the solvent is distilled off to obtain an aqueous resin dispersion (Q). (2) A solution (for example, an organic solvent solution described below) of a polyurethane prepolymer (P) having an isocyanate group at its end and containing a high molecular weight polyol (A) containing a hydroxyl group-containing polyolefin (A1) and an isocyanate component (B) as constituent monomers is prepared. Next, a mixture of water and, if necessary, a solvent, a neutralizing agent, and a chain extender (C) is charged and dispersed using a known dispersing machine, and if necessary, the solvent is distilled off to obtain an aqueous resin dispersion (Q).
[0099] (3) A solution (for example, a solvent solution described later) of a polyurethane prepolymer (P) having an isocyanate group at its end and containing a high molecular weight polyol (A) containing a hydroxyl group-containing polyolefin (A1) and an isocyanate component (B) as constituent monomers is prepared. Next, the mixture containing the above-mentioned (P) solution and water is dispersed using a known dispersing machine, and then, if necessary, a neutralizing agent and a reaction terminator are added, and further, if necessary, the solvent is distilled off to obtain an aqueous resin dispersion (Q). (4) A solvent solution of a polyurethane resin (U) containing, as constituent monomers, a high molecular weight polyol (A) containing a hydroxyl group-containing polyolefin (A1) and an isocyanate component (B) is prepared. Next, water is added, and the mixture is dispersed, for example, by a disperser, and if necessary, the solvent is distilled off to obtain an aqueous resin dispersion (Q).
[0100] In the step of obtaining the aqueous resin dispersion (Q), a known anionic surfactant, cationic surfactant, amphoteric surfactant, or nonionic surfactant may be used, if necessary, in addition to the polyurethane prepolymer (P), the solvent, the neutralizing agent, the chain extender (C), water, and the reaction terminator.
[0101] Examples of the solvent include organic solvents such as ketone-based solvents (e.g., acetone and methyl ethyl ketone), ester-based solvents [e.g., ethyl acetate and dibasic acid ester (DBE)], ether-based solvents (e.g., tetrahydrofuran), amide-based solvents (e.g., N,N-dimethylformamide and N-methylpyrrolidone), alcohol-based solvents (e.g., isopropyl alcohol), and aromatic hydrocarbon-based solvents (e.g., toluene). Furthermore, (Q) may contain the above-mentioned solvent.
[0102] As a method for incorporating the binder resin other than the polyurethane resin (U) as an aqueous resin dispersion in the electrode binder for a nonaqueous electrolyte secondary battery, the binder resin other than the polyurethane resin (U) is mixed with a solution of the urethane prepolymer (P) or the polyurethane resin (U) and then dispersed by the above-mentioned method, whereby an aqueous resin dispersion-like electrode binder for a nonaqueous electrolyte secondary battery containing the binder resin other than the polyurethane resin (U) can be obtained.
[0103] The solid content concentration (content of components other than volatile components) of the electrode binder for non-aqueous electrolyte secondary batteries is preferably 20 to 65% by weight, more preferably 25 to 55% by weight, from the viewpoint of ease of handling of the electrode binder for non-aqueous electrolyte secondary batteries. The solid content concentration can be obtained by thinly spreading about 1 g of the electrode binder for non-aqueous electrolyte secondary batteries on a Petri dish, precisely weighing it, and then heating it at 130°C for 45 minutes using a circulating constant temperature dryer, and then precisely weighing the weight, and calculating the ratio (percentage) of the remaining weight after heating to the weight before heating.
[0104] From the viewpoint of handling, the electrode binder for nonaqueous electrolyte secondary batteries has a viscosity of preferably 10 to 100,000 mPa·s, and more preferably 10 to 5,000 mPa·s at 25° C. The viscosity can be measured at a constant temperature of 25° C. using a BL type viscometer.
[0105] From the viewpoint of blend stability, the pH of the electrode binder for non-aqueous electrolyte secondary batteries is preferably 2 to 12, and more preferably 4 to 10. The pH can be measured at 25° C. using a pH Meter M-12 (manufactured by Horiba, Ltd.).
[0106] When the polyurethane resin (U) in the electrode binder for non-aqueous electrolyte secondary batteries of the present invention is in the form of an aqueous resin dispersion, the volume average particle size (Dv) of the particles of (U) is preferably 0.01 to 1 μm, more preferably 0.02 to 0.7 μm, and particularly preferably 0.03 to 0.4 μm, from the viewpoint of dispersion stability. When (Dv) is 0.01 μm or more, the viscosity is appropriate and the handling property is good, and when it is 1 μm or less, the dispersion stability is good.
[0107] The volume average particle diameter (Dv) can be controlled by the amount of ionic polar groups in (U) and the type and operating conditions of a dispersing machine used in the dispersing step.
[0108] [Non-aqueous electrolyte secondary battery electrode] The electrode for a non-aqueous electrolyte secondary battery of the present invention includes the resin composition for electrode binders for non-aqueous electrolyte secondary batteries of the present invention, an active material (a positive electrode active material for a positive electrode, and a negative electrode active material for a negative electrode), and a metal current collector. If necessary, a conductive assistant (carbon material such as carbon black, amorphous whisker carbon, graphite, etc.) may be added to the electrode.
[0109] Positive electrode active materials for lithium-ion batteries include transition metal oxides (MnO2, V2O5, etc.), transition metal sulfides (MoS2, TiS2, etc.), composite oxides of lithium and transition metals (LiCoO2, LiMnO2, LiMn2O4, LiNiO2, LiNi X Co (1-X) O2, etc.), and conductive polymer materials (polyaniline, polythiophene, polypyrrole, polyacetylene, polyacene, dimercaptothiadiazole / polyaniline composites, etc.).
[0110] Furthermore, the negative electrode active material for lithium ion batteries can be doped / dedoped with lithium ions, and examples of such materials include metallic lithium, lithium alloys, tin oxide, niobium oxide, vanadium oxide, titanium oxide, silicon-based active materials (silicon-lithium alloys, SiO, etc.), transition metal nitrides, and carbon-based materials (natural graphite, artificial graphite, etc.). These may be used as composites (metallic lithium-niobium oxide composites, etc.).
[0111] The metal current collectors of the positive and negative electrodes may be made of any conductive material, such as aluminum, nickel, copper, etc. The thickness of the current collector is generally 5 to 50 μm. The shape of the current collector may be a foil, a film, a sheet, a net, a punched one, a porous body, a foam, a fiber group, a molded nonwoven fabric, etc.
[0112] The secondary battery electrodes are specifically manufactured as follows. A binder paste is prepared by mixing an electrode binder for a non-aqueous electrolyte secondary battery, which contains the resin composition for electrode binders for non-aqueous electrolyte secondary batteries of the present invention, a positive electrode active material or a negative electrode active material, and, if necessary, a conductive assistant, a thickener (such as carboxymethyl cellulose), and an organic solvent in any order at room temperature or a controlled temperature. The binder paste is then applied onto a metal current collector and dried to form a secondary battery electrode. The weight ratio of the resin composition for electrode binders for nonaqueous electrolyte secondary batteries of the present invention to the positive electrode active material or the negative electrode active material is preferably 1 / 99 to 20 / 80, and more preferably 5 / 95 to 10 / 90, from the viewpoints of the adhesiveness of the resin composition for binders and the electric capacity of the secondary battery.
[0113] The paste can be applied to the metal current collector using, for example, a film applicator or a doctor blade. In addition, the method for removing water and / or organic solvent after coating on the metal current collector includes, for example, drying at 60 to 150° C., preferably 70 to 130° C., for 5 to 120 minutes, and further drying under reduced pressure at 80 to 120° C. for 1 to 12 hours. The thickness of the coating film on the electrode after coating and drying is preferably 10 to 500 μm from the viewpoint of the electric capacity and cycle characteristics of the secondary battery described below. The thickness and density of the coating film on the electrode can be controlled by compression molding at a predetermined pressure, for example, using a roll press machine.
[0114] [Nonaqueous electrolyte secondary battery] The nonaqueous electrolyte secondary battery of the present invention is produced by sealing the electrodes (positive and negative electrodes), separator, and electrolyte of the present invention in a container. Examples of the separator include a porous membrane and a nonwoven fabric, and examples of the porous membrane include polyolefin, polyimide, polyvinylidene fluoride, polyester, etc. Examples of the nonwoven fabric include polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, glass fiber, etc. Examples of the shape of the nonaqueous electrolyte secondary battery include a cylindrical type, a coin type, a square type, a film type, etc.
[0115] Non-aqueous electrolyte secondary batteries include non-aqueous electrolytes used in lithium ion secondary batteries, such as LiPF6, LiBF4, LiClO4, LiAsF6, CF3SO3Li, (CF3SO2)2N / Li, dissolved alone or in combination of two or more in an organic solvent (diethyl carbonate, ethylene carbonate, ethyl methyl carbonate, propylene carbonate, γ-butyrolactone, etc.).
[0116] The resin composition for a non-aqueous electrolyte secondary electrode binder of the present invention has excellent resistance to swelling in an electrolyte and excellent adhesion between each active material of a positive electrode and each metal current collector of a negative electrode. The swelling resistance can be evaluated by an electrolyte swelling test described later, and the adhesion can be evaluated by a peel test described later. In addition, a nonaqueous electrolyte secondary battery having an electrode formed using the resin composition for electrode binders for nonaqueous electrolyte secondary batteries of the present invention is electrochemically stable and has an excellent battery capacity retention rate after a high-voltage charge-discharge cycle test described later.
[0117] INDUSTRIAL APPLICABILITY The resin composition for electrode binders for non-aqueous electrolyte secondary batteries of the present invention can be suitably used for applications as electrode binders for non-aqueous electrolyte secondary batteries. EXAMPLES
[0118] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.
[0119] <Production Example 1> A reaction vessel was charged with 1,000 parts by weight of polyolefin (A00-1) whose constituent monomers were 91% by weight of propylene and 9% by weight of ethylene [Mn: 113,000, isotacticity: 50%, product name "Vistamaxx3980", manufactured by Exxonmobil], and while aerating nitrogen into the liquid phase, the mixture was heated and melted using a mantle heater. Thermal degradation was then carried out with stirring at 370°C for 85 minutes, yielding polyolefin (A01-1). In a reaction vessel, 100 parts by weight of the obtained polyolefin (A01-1) and 6.5 parts by weight of maleic anhydride (E-1) (weight parts after subtracting the distilled amount described below. The same applies to the following production examples) were charged, and after nitrogen replacement, the mixture was heated to 180°C under nitrogen aeration to dissolve uniformly, and a solution of 0.5 parts by weight of a radical initiator [dicumyl peroxide, trade name "Percumyl D", NOF Corp.] (F-1) dissolved in 5 parts by weight of xylene was dropped over 5 minutes, and stirring was continued for 1 hour under xylene reflux. Then, unreacted maleic anhydride was distilled off under reduced pressure (1.5 kPa) to obtain acid-modified polyolefin (X-1). Next, 100 parts by weight of (X-1) and 6.4 parts by weight of 2-aminoethanol (G-1) (weight parts are shown after subtracting the amount distilled off, which will be described later. The same applies to the following Production Examples) were charged into a reaction vessel, and reacted at 180°C for 1 hour under a nitrogen gas atmosphere. Next, unreacted 2-aminoethanol was distilled off at 180° C. under a reduced pressure of 2.7 kPa to obtain a hydroxyl group-containing polyolefin (A1-1). The hydroxyl value of (A1-1) was 29, the acid value was 0.2, the Mn was 3,500, and the isotacticity was 43%. The number of double bonds per 1,000 carbons of the polyolefin (A01-1) used for modification was 7.5.
[0120] <Production Example 2> A reaction vessel was charged with 1,000 parts by weight of polyolefin (A00-1) whose constituent monomers were 91% by weight of propylene and 9% by weight of ethylene [Mn: 113,000, isotacticity: 50%, product name "Vistamaxx3980", manufactured by Exxonmobil], and while aerating nitrogen into the liquid phase, the mixture was heated and melted using a mantle heater. Thermal degradation was then carried out with stirring at 380°C for 65 minutes, yielding polyolefin (A01-2). In a reaction vessel, 100 parts by weight of the obtained polyolefin (A01-2) and 8 parts by weight of maleic anhydride (E-1) were charged, and after replacing with nitrogen, the mixture was heated to 180°C under nitrogen aeration to dissolve uniformly, and stirring was continued for 1 hour. After that, unreacted maleic anhydride was distilled off under reduced pressure (1.5 kPa) to obtain an acid-modified polyolefin (X-2). Next, 100 parts by weight of (X-2) and 6.4 parts by weight of 2-aminoethanol (G-1) were charged into a reaction vessel, and the mixture was reacted at 180° C. for 1 hour under a nitrogen gas atmosphere. Next, unreacted 2-aminoethanol was distilled off at 180° C. under a reduced pressure of 2.7 kPa to obtain a hydroxyl group-containing polyolefin (A1-2). The hydroxyl value of (A1-2) was 29, the acid value was 0.1, the Mn was 3,300, and the isotacticity was 43%. The number of double bonds per 1,000 carbons of the polyolefin (A01-2) used for modification was 8.8.
[0121] <Production Example 3> A reaction vessel was charged with 1,000 parts by weight of polyolefin (A00-2) whose constituent monomers were 85% by weight of propylene and 15% by weight of ethylene [Mn: 76,000, isotacticity: 20%, product name "Vistamaxx6202", manufactured by Exxonmobil], and while aerating nitrogen into the liquid phase, the mixture was heated and melted using a mantle heater. Then, while stirring, the mixture was thermally degraded at 400°C for 50 minutes to obtain polyolefin (A01-3). In a reaction vessel, 100 parts by weight of the obtained polyolefin (A01-3) and 11 parts by weight of maleic anhydride (E-1) were charged, and after nitrogen replacement, the mixture was heated to 180°C under nitrogen aeration to dissolve uniformly, and a solution in which 3 parts by weight of a radical initiator [dicumyl peroxide, trade name "Percumyl D", NOF Corp.] (F-1) was dissolved in 10 parts by weight of xylene was dropped over 5 minutes, and stirring was continued for 1 hour under xylene reflux. Then, unreacted maleic anhydride was distilled off under reduced pressure (1.5 kPa) to obtain acid-modified polyolefin (X-3). Next, 100 parts by weight of (X-3) and 10 parts by weight of 2-aminoethanol (G-1) were charged into a reaction vessel, and the mixture was reacted at 180° C. for 1 hour under a nitrogen gas atmosphere. Next, unreacted 2-aminoethanol was distilled off at 180° C. under a reduced pressure of 2.7 kPa to obtain a hydroxyl group-containing polyolefin (A1-3). The hydroxyl value of (A1-3) was 46, the acid value was 0.1, the Mn was 2,300, and the isotacticity was 18%. The number of double bonds per 1,000 carbons of the polyolefin (A01-3) used for modification was 9.5.
[0122] <Production Example 4> A reaction vessel was charged with 1,000 parts by weight of polyolefin (A00-2) whose constituent monomers were 85% by weight of propylene and 15% by weight of ethylene [Mn: 76,000, isotacticity: 20%, product name "Vistamaxx6202", manufactured by Exxonmobil], and while aerating nitrogen into the liquid phase, the mixture was heated and melted using a mantle heater. Then, while stirring, the mixture was thermally degraded at 400°C for 100 minutes to obtain polyolefin (A01-4). In a reaction vessel, 100 parts by weight of the obtained polyolefin (A01-4) and 23.5 parts by weight of maleic anhydride (E-1) were charged, and after nitrogen replacement, the mixture was heated to 180°C under nitrogen aeration to dissolve uniformly, and a solution in which 3 parts by weight of a radical initiator [dicumyl peroxide, trade name "Percumyl D", NOF Corp.] (F-1) was dissolved in 10 parts by weight of xylene was dropped over 5 minutes, and stirring was continued for 1 hour under xylene reflux. Then, unreacted maleic anhydride was distilled off under reduced pressure (1.5 kPa) to obtain acid-modified polyolefin (X-4). Next, 100 parts by weight of (X-4) and 27 parts by weight of 2-aminoethanol (G-1) were charged into a reaction vessel, and the mixture was reacted at 180° C. for 1 hour under a nitrogen gas atmosphere. Next, unreacted 2-aminoethanol was distilled off at 180° C. under a reduced pressure of 2.7 kPa to obtain a hydroxyl group-containing polyolefin (A1-4). The hydroxyl value of (A1-4) was 108, the acid value was 0.2, the Mn was 1,050, and the isotacticity was 17%. The number of double bonds per 1,000 carbons of the polyolefin (A01-4) used for modification was 22.4.
[0123] <Production Example 5> A reaction vessel was charged with 1,000 parts by weight of polyolefin (A00-3) whose constituent monomers were 73% by weight of propylene and 27% by weight of ethylene [Mn: 200,000, isotacticity: 33%, product name "Tafmer S4030", manufactured by Mitsui Chemicals], and while aerating nitrogen into the liquid phase, the mixture was heated and melted using a mantle heater. Then, while stirring, the mixture was thermally degraded at 380°C for 80 minutes to obtain polyolefin (A01-5). In a reaction vessel, 100 parts by weight of the obtained polyolefin (A01-5) and 4.5 parts by weight of maleic anhydride (E-1) were charged, and after nitrogen replacement, the mixture was heated to 180°C under nitrogen aeration to dissolve uniformly, and a solution in which 0.5 parts by weight of a radical initiator [dicumyl peroxide, trade name "Percumyl D", NOF Corp.] (F-1) was dissolved in 5 parts by weight of xylene was dropped over 5 minutes, and stirring was continued for 1 hour under xylene reflux. Then, unreacted maleic anhydride was distilled off under reduced pressure (1.5 kPa) to obtain acid-modified polyolefin (X-5). Next, 100 parts by weight of (X-5) and 4.6 parts by weight of 2-aminoethanol (G-1) were charged into a reaction vessel, and the mixture was reacted at 180° C. for 1 hour under a nitrogen gas atmosphere. Next, unreacted 2-aminoethanol was distilled off at 180° C. under a reduced pressure of 2.7 kPa to obtain a hydroxyl group-containing polyolefin (A1-5). The hydroxyl value of (A1-5) was 21, the acid value was 0.2, the Mn was 4,500, and the isotacticity was 31%. The number of double bonds per 1,000 carbons of the polyolefin (A01-5) used for modification was 5.4.
[0124] <Comparative Manufacturing Example 1> A reaction vessel was charged with 1000 parts by weight of polyolefin (comparison A00-1) whose constituent monomers were 98% by weight of propylene and 2% by weight of ethylene [Mn: 100,000, isotacticity: 90%, product name "SunAllomer PZA20A", manufactured by SunAllomer Co., Ltd.], and while aerating nitrogen into the liquid phase, the mixture was heated and melted using a mantle heater. Thermal degradation was then carried out with stirring at 400°C for 1200 minutes, yielding polyolefin (comparison A01-1). In a reaction vessel, 100 parts by weight of the obtained polyolefin (comparison A01-1) and 28 parts by weight of maleic anhydride (E-1) were charged, and after nitrogen replacement, the mixture was heated to 180°C under nitrogen aeration to dissolve uniformly, and a solution in which 3 parts by weight of a radical initiator [dicumyl peroxide, trade name "Percumyl D", NOF Corp.] (F-1) was dissolved in 10 parts by weight of xylene was dropped over 5 minutes, and stirring was continued for 1 hour under xylene reflux. Then, unreacted maleic anhydride was distilled off under reduced pressure (1.5 kPa) to obtain an acid-modified polyolefin (comparison X-1). Next, 100 parts by weight of (composition X-1) and 22 parts by weight of 2-aminoethanol (G-1) were charged into a reaction vessel, and the mixture was reacted at 180° C. for 1 hour under a nitrogen gas atmosphere. Next, unreacted 2-aminoethanol was distilled off at 180° C. under a reduced pressure of 2.7 kPa to obtain a hydroxyl group-containing polyolefin (comparison A1-1). The hydroxyl value of (Comparative A1-1) was 122, the acid value was 0.2, the Mn was 940, and the isotacticity was 84%. The number of double bonds per 1,000 carbons of the polyolefin (Comparative A01-1) used for modification was 22.5.
[0125] <Comparative Manufacturing Example 2> A reaction vessel was charged with 1,000 parts by weight of a polyolefin (comparison A00-2) whose constituent monomers were 27% by weight of propylene and 73% by weight of ethylene [Mn: 40,000, isoactivity: 3%, product name "TAFMER P0280", manufactured by Mitsui Chemicals, Inc.], and while aerating nitrogen into the liquid phase, the mixture was heated and melted using a mantle heater. While stirring, the mixture was thermally degraded at 385°C for 210 minutes to obtain a polyolefin (comparison A01-2). In a reaction vessel, 100 parts by weight of the obtained polyolefin (comparison A01-2) and 9 parts by weight of maleic anhydride (E-1) were charged, and after nitrogen replacement, the mixture was heated to 180°C under nitrogen aeration to dissolve uniformly, and a solution in which 0.5 parts by weight of a radical initiator [dicumyl peroxide, trade name "Percumyl D", NOF Corp.] (F-1) was dissolved in 5 parts by weight of xylene was dropped over 5 minutes, and stirring was continued for 1 hour under xylene reflux. Then, unreacted maleic anhydride was distilled off under reduced pressure (1.5 kPa) to obtain an acid-modified polyolefin (comparison X-2). Next, 100 parts by weight of (composition X-2) and 10 parts by weight of 2-aminoethanol (G-1) were charged into a reaction vessel, and reacted at 180° C. for 1 hour under a nitrogen gas atmosphere. Next, unreacted 2-aminoethanol was distilled off at 180° C. under a reduced pressure of 2.7 kPa to obtain a hydroxyl group-containing polyolefin (comparison A1-2). The hydroxyl value of (Comparative A1-2) was 35, the acid value was 0.1, the Mn was 3,000, and the isotacticity was 1%. The number of double bonds per 1,000 carbons of the polyolefin (Comparative A01-2) used for modification was 10.5.
[0126] <Example 1> (Preparation of urethane prepolymer) A simple pressurized reaction apparatus equipped with a stirrer and a heater was charged with 179.26 parts by weight of hydroxyl-containing polyolefin (A1-1), 92.19 parts by weight of polymer polyol (A2-1), 82.65 parts by weight of isocyanate component (B-1) [IPDI, isophorone diisocyanate], 4.18 parts by weight of [1,4-butanediol] as chain extender (C), 17.03 parts by weight of [2,2-dimethylolpropionic acid], and 124.69 parts by weight of organic solvent [THF, tetrahydrofuran], and stirred at 85°C for 10 hours to carry out a urethane reaction, producing a THF solution of urethane prepolymer (P-1). (Preparation of aqueous resin dispersion (Q-1) containing resin composition (N-1) for electrode binder for non-aqueous electrolyte secondary battery and water) A simple pressure reaction apparatus equipped with an agitator and a heating reaction apparatus was charged with 500.00 parts by weight of the obtained urethane prepolymer THF solution (P-1), and 359.28 parts by weight of THF and 12.81 parts by weight of triethylamine (neutralizer) were added while stirring at 50 ° C., and the mixture was homogenized at 60 rpm for 30 minutes. After that, the temperature was kept at 50 ° C., and 676.04 parts by weight of ion-exchanged water was gradually added while stirring at 500 rpm to emulsify the mixture. Then, 86.82 parts by weight of a chain extender (C-3) [5 wt% diethylenetriamine aqueous solution] was added, and THF was distilled off under reduced pressure at 65 ° C. for 12 hours to obtain an aqueous resin dispersion (Q-1) containing the resin composition (N-1) for electrode binders for non-aqueous electrolyte secondary batteries and water.
[0127] <Examples 2 to 25 and Comparative Examples 1 to 3> In Example 1, except that the raw materials used were as shown in Tables 1 to 4, the same procedure as in Example 1 was carried out to obtain aqueous resin dispersions (Q-2) to (Q-25) and (Q-1) to (Q-3), each containing resin compositions (N-2) to (N-25) and (N-1) to (N-3) for electrode binders for non-aqueous electrolyte secondary batteries and water.
[0128] The obtained aqueous resin dispersions (Q-1) to (Q-25) and (Comparative Q-1) to (Comparative Q-3) were evaluated according to the procedures described below. The results are shown in Tables 1 to 4.
[0129] The volume average particle diameter (Dv) was measured using a laser diffraction particle size distribution analyzer "LA-750" (manufactured by Horiba, Ltd.).
[0130] [Table 1]
[0131] [Table 2]
[0132] [Table 3]
[0133] [Table 4]
[0134] The raw materials used in the examples and comparative examples are as follows. High molecular weight polyol (A2-1): Kuraray Polyol P-2010: Poly(3-methyl-1,5-pentanediol, adipic acid polycondensate) with Mn=2,000, manufactured by Kuraray Co., Ltd. High molecular weight polyol (A2-2): Kuraray Polyol P-2011: Poly(3-methyl-1,5-pentanediol, adipic acid, and terephthalic acid polycondensate) with Mn=2,000, manufactured by Kuraray Co., Ltd. High molecular weight polyol (A2-3): Kuraray Polyol P-2012: Poly(3-methyl-1,5-pentanediol, adipic acid, isophthalic acid polycondensate) with Mn=2,000, manufactured by Kuraray Co., Ltd. High molecular weight polyol (A2-4): Kuraray Polyol P-2020: Poly(3-methyl-1,5-pentanediol, terephthalic acid polycondensate) with Mn=2,000, manufactured by Kuraray Co., Ltd. Polymer polyol (A4-1): Ethanacole UH-200: Polyhexamethylene carbonate diol with Mn=2,000 [manufactured by Ube Industries, Ltd.] Polymer polyol (A5-1): PTMG2000: Poly(oxytetramethylene) glycol with Mn=2,000 [Mitsubishi Chemical Co., Ltd.] Polymer polyol (A5-2): PTMG3000: Poly(oxytetramethylene) glycol with Mn=3,000 [Mitsubishi Chemical Co., Ltd.] Polymer polyol (A6-1): Actflow UT-1001: Polyacrylic diol with Mn=2000 [manufactured by Soken Chemical Industries, Ltd.] Polymer polyol (A6-2): ARUFON UH-2032: Polyacrylic diol with Mn=2000 [manufactured by Toagosei Co., Ltd.] Neostan U-600: Bismuth tris(2-ethylhexanoate) [manufactured by Nitto Kasei Co., Ltd.] Emulmin 50: Ethylene oxide (EO) adduct of higher alcohol [manufactured by Sanyo Chemical Industries, Ltd.]
[0135] <Evaluation method> [1] Electrolyte swelling test (evaluation of swelling resistance) The aqueous resin dispersion (Q) was poured into a polypropylene mold measuring 10 cm long x 20 cm wide x 1 cm deep in an amount that would result in a film thickness of 200 μm after drying, and the film was dried at room temperature for 12 hours, and then heated and dried in a circulating air dryer at 105°C for 3 hours. The film obtained was cut into 2 cm x 8 cm to prepare a test piece, and its weight (W0) was measured using an electronic balance capable of measuring to four decimal places. The test piece was immersed in an electrolyte solution prepared by adding 3 parts by weight of vinylene carbonate to 100 parts by weight of a mixed solvent of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate (volume ratio 3:3:2) and further dissolving lithium hexafluorophosphate to a concentration of 1 mol / L at 50°C for 24 hours, and the weight (W1) of the test piece after immersion in the electrolyte solution was measured, and the increase in weight was calculated using the following formula, and the electrolyte expansion rate (%) was evaluated according to the following criteria. Electrolyte expansion rate (%) = [(W1)-(W0)] x 100 / (W0) W0: Weight of the test piece before immersion in the electrolyte W1: Weight of the test piece after immersion in the electrolyte Evaluation criteria ⊚: The electrolyte expansion rate is less than 10%. ◯: The electrolyte expansion rate is 10% or more and less than 15%. △: The electrolyte expansion rate is 15% or more and less than 25%. ×: The electrolyte expansion rate is 25% or more.
[0136] [2] Peel test (evaluation of adhesion) <Creating a positive electrode for evaluating adhesion> The aqueous resin dispersion (Q) was diluted with ion-exchanged water to a solid content concentration of 24% by weight to obtain 20.8 parts by weight of a dispersion, 90.0 parts by weight of lithium cobalt oxide [trade name "Cellseed C", manufactured by Nippon Chemical Industry Co., Ltd.] as a positive electrode active material, 5.0 parts by weight of acetylene black ["Denka Black", manufactured by Denka Co., Ltd. (hereinafter the same)] as a conductive assistant, and 25 parts by weight of ion-exchanged water were mixed and kneaded for 5 minutes with a kneader ("Awatori Rentaro", manufactured by Thinky Corporation) to prepare a positive electrode slurry. The slurry was applied to one side of an aluminum electrolytic foil having a thickness of 20 μm using a film applicator so that the thickness after drying was about 10 μm, and the coating was dried at 80 ° C. for 1 hour, and then further dried under reduced pressure (1.3 kPa) at 80 ° C. for 2 hours to obtain a test piece of a positive electrode having a thickness of 30 μm in which an active material layer was formed on the aluminum electrolytic foil.
[0137] <Creating a negative electrode for evaluating adhesion> The aqueous resin dispersion (Q) was diluted with ion-exchanged water to a solid content concentration of 24% by weight, and 31.3 parts by weight of the dispersion was mixed with 92.5 parts by weight of graphite powder [trade name "CGC-20", manufactured by Nippon Graphite Industries Co., Ltd.] as a negative electrode active material, and 25 parts by weight of ion-exchanged water. Then, a negative electrode slurry was prepared in the same manner as the positive electrode. The slurry was applied to one side of a copper foil having a thickness of 20 μm using a film applicator so that the thickness after drying was about 10 μm, and the coating was dried at 80° C. for 1 hour, and then further dried at 80° C. under reduced pressure (1.3 kPa) for 2 hours to obtain a negative electrode test piece having an active material layer formed on the copper foil and a thickness of 30 μm.
[0138] <Peel test (evaluation of adhesion)> The obtained positive and negative electrodes of the secondary battery were each cut to 20 mm long x 20 mm wide, and cut every 1 mm with a cutter knife to create a grid of 100 squares. Cellophane tape (registered trademark) was applied to the grid, and the tape was peeled off in one go. The number of squares that did not peel off out of the 100 squares was used to evaluate the performance according to the following criteria. <Evaluation criteria> ◎: 98-100 squares that did not peel off ○: 90-98 squares that did not peel off ×: Fewer than 90 squares were not peeled off
[0139] [3] Evaluation of high-voltage charge / discharge cycle characteristics <Preparation of lithium-ion batteries for evaluation of high-voltage charge / discharge cycle characteristics of positive electrodes> A part of the positive electrode test piece prepared for adhesiveness evaluation was punched out to 15.95 mmφ and used as the positive electrode. The negative electrode was prepared by thoroughly mixing 92.5 parts by weight of graphite powder, 7.5 parts by weight of polyvinylidene fluoride (Sigma-Aldrich Co., Ltd.), and 200 parts by weight of 1-methyl-2-pyrrolidone (Tokyo Chemical Industry Co., Ltd.) in a mortar to obtain a slurry, applying the obtained slurry to one side of a copper foil having a thickness of 20 μm in the atmosphere using a wire bar, drying at 80 ° C for 1 hour, and then drying at 80 ° C for 2 hours under reduced pressure (1.3 kPa), and punching out to 16.15 mmφ. The positive and negative electrodes were placed at both ends of a 2032-type coin cell with their coating surfaces facing each other, and a separator (nonwoven polypropylene fabric) was inserted between the electrodes to prepare a lithium-ion battery cell. An electrolyte solution was prepared by dissolving LiPF6 as an electrolyte in a mixed solvent of ethylene carbonate and diethyl carbonate (volume ratio 1:1) so that the content was 12% by weight based on the weight of the mixed solvent. The prepared electrolyte solution was poured into the cell and sealed to prepare a lithium-ion battery for evaluating high-voltage charge-discharge cycle characteristics.
[0140] <Preparation of lithium-ion batteries for evaluation of high-voltage charge / discharge cycle characteristics of negative electrodes> The positive electrode was prepared by thoroughly mixing 90.0 parts by weight of lithium cobalt oxide, 5 parts by weight of acetylene black, and 5 parts by weight of polyvinylidene fluoride in a mortar, adding 70.0 parts by weight of 1-methyl-2-pyrrolidone, and further mixing thoroughly in a mortar to obtain a slurry. The obtained slurry was applied to one side of an aluminum electrolytic foil having a thickness of 20 μm using a wire bar in the atmosphere, dried at 80 ° C for 1 hour, and then further dried at 80 ° C under reduced pressure (1.3 kPa) for 2 hours, and punched out to 15.95 mm φ. The negative electrode was prepared by punching out a part of the negative electrode test piece prepared for adhesion evaluation to 16.15 mm φ. A lithium ion battery for evaluating high voltage charge and discharge cycle characteristics was prepared in the same manner as the preparation of the lithium ion battery for evaluating high voltage charge and discharge cycle characteristics of the positive electrode, except for using the above positive electrode and negative electrode.
[0141] <Evaluation of high-voltage charge / discharge cycle characteristics> Using a charge / discharge measuring device "Battery Analyzer 1470" (manufactured by Toyo Corporation), the lithium ion battery prepared above was charged in a thermostatic chamber at 25°C at a current of 0.1C up to a voltage of 4.5V, and after a 10-minute pause, the battery voltage was discharged down to 3.5V at a current of 0.1C, and this charge / discharge cycle was repeated. The battery capacity at the first charge and the battery capacity at the 100th charge cycle were measured, and the high-voltage charge / discharge cycle characteristics were calculated using the following formula. The high-voltage charge / discharge cycle characteristics were evaluated according to the following criteria. High voltage charge / discharge cycle characteristics (%) = (battery capacity at 100th charge cycle / battery capacity at first charge) x 100 Evaluation criteria ⊚: High voltage charge / discharge cycle characteristic (%) is 95% or more. ◯: The high-voltage charge / discharge cycle characteristic (%) is 90% or more and less than 95%. △: High voltage charge / discharge cycle characteristic (%) is 85% or more and less than 90%. ×: The high voltage charge / discharge cycle characteristic (%) is less than 85%.
[0142] The results in Tables 3 and 4 show that the resin composition for electrode binders for nonaqueous electrolyte secondary batteries of the present invention and the aqueous resin dispersion for electrode binders for nonaqueous electrolyte secondary batteries (Q), which contains the resin composition for electrode binders for nonaqueous electrolyte secondary batteries of the present invention and water, are superior to the comparative examples in all of (1) swelling resistance to the electrolyte, (2) adhesion between each active material of the positive and negative electrodes and each electrode metal current collector, and (3) high-voltage charge / discharge cycle characteristics of a secondary battery having electrodes formed using the resin composition for electrode binders for nonaqueous electrolyte secondary batteries.
Claims
1. A resin composition for an electrode binder for a non-aqueous electrolyte secondary battery, comprising a polyurethane resin (U), the polyurethane resin (U) being a polyurethane resin obtained by reacting an active hydrogen group-containing compound (W) with an isocyanate component (B), the active hydrogen group-containing compound (W) comprising a polymer polyol (A), the polymer polyol (A) comprising a hydroxyl group-containing polyolefin (A1), the hydroxyl group-containing polyolefin (A1) having a carbon-carbon double bond modified with an unsaturated (poly)carboxylic acid (anhydride) (E). A resin composition for electrode binders for non-aqueous electrolyte secondary batteries, which is a reaction product of an acid-modified polyolefin (X), which is a polyolefin (A01), with an aminoalcohol (G), or a reaction product of the acid-modified polyolefin (X) with an alkylene oxide, wherein the weight ratio [ethylene / α-olefin] of ethylene, which is a constituent monomer of the hydroxyl group-containing polyolefin (A1), to an α-olefin is 5 / 95 to 65 / 35, and the isotacticity of the α-olefin portion of the hydroxyl group-containing polyolefin (A1) is 1 to 50%.
2. 2. The resin composition for electrode binders in non-aqueous electrolyte secondary batteries in accordance with claim 1, wherein the hydroxyl-containing polyolefin (A1) has a hydroxyl value (mg KOH / g) of 12 to 120.
3. 3. An electrode binder for a non-aqueous electrolyte secondary battery, comprising the resin composition for an electrode binder for a non-aqueous electrolyte secondary battery according to claim 1 or 2.
4. 3. An electrode for a non-aqueous electrolyte secondary battery, comprising an active material, a metal current collector, and the resin composition for an electrode binder for a non-aqueous electrolyte secondary battery according to claim 1 or 2.
5. A nonaqueous electrolyte secondary battery comprising an electrolyte, a separator, and the electrode for a nonaqueous electrolyte secondary battery according to claim 4.
Citation Information
Patent Citations
Electrode film for non-aqueous electrolyte secondary battery
JP1997251856A
Coating agent for polyolefin
JP2002241691A
Binder for printing ink, and printing ink composition
JP2006274048A
Composition for nonaqueous secondary battery electrode and nonaqueous secondary battery using the same
JP2012204010A
Secondary battery electrode binder, slurry, secondary battery electrode and secondary battery
JP2016009544A
